Autopolyploid inheritance and a heterozygous reciprocal translocation shape chromosome genetic behavior in tetraploid blueberry (Vaccinium corymbosum). Issue 3 (3rd September 2022) - Mengist, Molla F.; Bostan, Hamed; De Paola, Domenico; Teresi, Scott J.; Platts, Adrian E.; Cremona, Gaetana; Qi, Xinpeng; Mackey, Ted; Bassil, Nahla V.; Ashrafi, Hamid; Giongo, Lara; Jibran, Rubina; et al.
Summary: Understanding chromosome recombination behavior in polyploidy species is key to advancing genetic discoveries. In blueberry, a tetraploid species, the line of evidences about its genetic behavior still remain poorly understood, owing to the inter‐specific, and inter‐ploidy admixture of its genome and lack of in depth genome‐wide inheritance and comparative structural studies. Here we describe a new high‐quality, phased, chromosome‐scale genome of a diploid blueberry, clone W85. The genome was integrated with cytogenetics and high‐density, genetic maps representing six tetraploid blueberry cultivars, harboring different levels of wild genome admixture, to uncover recombination behavior and structural genome divergence across tetraploid and wild diploid species. Analysis of chromosome inheritance and pairing demonstrated that tetraploid blueberry behaves as an autotetraploid with tetrasomic inheritance. Comparative analysis demonstrated the presence of a reciprocal, heterozygous, translocation spanning one homolog of chr‐6 and one of chr‐10 in the cultivar Draper. The translocation affects pairing and recombination of chromosomes 6 and 10. Besides the translocation detected in Draper, no other structural genomic divergences were detected across tetraploid cultivars and highly inter‐crossable wild diploid species. These findings and resources will facilitate new genetic and comparative genomic studies in Vaccinium and the development of genomic assisted selection strategy for this crop.